2021
DOI: 10.20473/jisebi.7.2.162-172
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption in Small-Medium Enterprises based on Technology Acceptance Model: A Critical Review

Abstract: Background: Technology acceptance model (TAM) has been extensively used to analyse user acceptance of technologies adopted by enterprises at different levels. Moreover, the technology adoption has drawn attention among practitioners and academic communities alike, leading to the development of approaches to understand the concept. However, there is a degree of inconsistency found in previous studies on different types of TAM models used in explaining user acceptance of technologies among small-medium enterpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Consequently, if the perceived usefulness of e-commerce rises, there will be a corresponding increase in the inclination to use e-commerce. This finding aligns with the research conducted by [6], [8], [14], [15], [16], [24], [31]. However, it differs from studies conducted on Thai SMEs, where perceived usefulness was not found to be a significant factor [32].…”
Section: 867supporting
confidence: 85%
See 1 more Smart Citation
“…Consequently, if the perceived usefulness of e-commerce rises, there will be a corresponding increase in the inclination to use e-commerce. This finding aligns with the research conducted by [6], [8], [14], [15], [16], [24], [31]. However, it differs from studies conducted on Thai SMEs, where perceived usefulness was not found to be a significant factor [32].…”
Section: 867supporting
confidence: 85%
“…The TAM model consists of three variables: attitude towards utilizing technology or systems (ATU), perceived usefulness (PU), and perceived ease of use (PEOU) [9]. The TAM model was utilized in research conducted by [6], [8], [10], [11], [12], [13], [14], [15], [16], [17] to investigate technology adoption. The Technology-Organization-Environment (TOE) framework is commonly employed in studies on the adoption of technology in organizational settings.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan's Mobile Suica, social influence is indeed significant with in adoption of electronic wallets [20]. In India, social influence has also been discovered as a significant factor of customer's intention to employ a digital wallet service [23].…”
Section: Hypotheses Testmentioning
confidence: 99%
“…Technology Acceptance Model (TAM) is a theory that is widely used in the field of technology and innovation management for technology and innovation that occurs, spreads, or is widely accepted and used in society (Davis, 1989). In this study, Technology Acceptance Model (TAM) was applied to study the factors affecting the adoption of digital technology among Thai SMEs (Nurqamarani, Soegiarto & Nurlaeli, 2021). The principle of TAM is the study of factors that influence the adoption and use of new things, whether new products to the market, technology, and innovation, etc.…”
Section: Literature Reviewmentioning
confidence: 99%